Upaya Mengurangi Resiko Ancaman Banjir melalui Edukasi dan Pelatihan Biopori berbasis Sampah Organik dan Botol Plastik di Kelurahan Jatirejo Semarang - Andin Vita Amalia; Rizki Nor Amelia; Amnan Haris; Erna Noor Savitri; Parmin Parmin; Abdul Jabbar (Jurnal Dharma Indonesia, 2023)
Jatirejo Village is a hilly area where some places tend to have depressions so that they are prone to puddles. Therefore, a system is needed that can help infiltrate water into the soil, one of which is biopori, based on organic waste and plastic bottles. This service aims to provide education related to biopores as well as train Jatirejo Village residents to make and apply biopores, especially in the basin area, to reduce the risk of flood threats. The methods used were lectures, discussions, and hands-on practices carried out in four stages, namely situation analysis and preparation, socialization, implementation, and evaluation. In general, the results of the analysis showed that the participants were satisfied with the training and that the training activities provided positive benefits, as evidenced by the significant increase in knowledge after the participants participated in the biopore training activities.